2023
DOI: 10.1096/fj.202200022rr
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA PDK1 targets miR‐4731‐5p to enhance TNXB expression in ligamentum flavum hypertrophy

Abstract: Hypertrophic ligamentum flavum (LF) is a main factor responsible for lumbar spinal stenosis (LSS); however, the exact mechanisms of the pathogenesis of these processes remain unknown. This study aimed to elucidate whether circular RNAs and microRNAs regulate the pathogenesis of LF and LSS, especially focusing on circPDK1 (hsa_circ_0057105), a circRNA targeting pyruvate dehydrogenase kinase 1 and differentially expressed in LF tissues between lumbar disk herniation and LSS patients. The circPDK1/miR-4731 and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Growing evidence shows that noncoding RNAs, including lncRNAs, play a role in the development and progression of various disorders, including spinal diseases [ 9 , 29 ]. Previous studies have investigated molecular mechanisms underlying LFH; however, the role of lncRNAs in LFH progression is only partially understood [ 22 , 23 , 30 , 31 ]. Here, we investigated the expression patterns of lncRNAs in LFH and LFN tissues by lncRNA sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence shows that noncoding RNAs, including lncRNAs, play a role in the development and progression of various disorders, including spinal diseases [ 9 , 29 ]. Previous studies have investigated molecular mechanisms underlying LFH; however, the role of lncRNAs in LFH progression is only partially understood [ 22 , 23 , 30 , 31 ]. Here, we investigated the expression patterns of lncRNAs in LFH and LFN tissues by lncRNA sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Although not related to the cancer field, it is worth mentioning that in a cell model of hypertrophic flavum ligamentum, LOXL2 mRNA is targeted by miR-4731, and LOXL2 downregulation is relieved by circPDK1 [ 90 ].…”
Section: Control Of Loxl2 Expressionmentioning
confidence: 99%
“…Circular RNAs (circRNAs), which are classified as noncoding RNA, exploit covalent bonds to form closed-loop structures [3,4]. Studies showed that circRNAs significantly impact the progression of fibrotic diseases [5][6][7]. The study of Zhang et al demonstrated that circPDK1 promoted the propagation, dissemination, and fibrosis of LF cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that circRNAs significantly impact the progression of fibrotic diseases [5][6][7]. The study of Zhang et al demonstrated that circPDK1 promoted the propagation, dissemination, and fibrosis of LF cells [7]. The expression profile of circRNA has revealed a significant downregulation of circ_0003609 in both HLF tissues and cells [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation